KAJIAN SUBSTITUSI TEPUNG TAPIOKA DAN PENAMBAHAN GLISEROL MONOSTEARAT PADA PEMBUATAN ROTI TAWAR - Basuki, Enny Karti; Yulistyani, Ratna; Hidayat, Roni (UPN VETERAN JAWA TIMUR, 2011)
Bread is one of fermentation product and consumer likely made form wheat flour , bread have difference taste and softness. Using cassava flour to product bread that can increased various bread product and value. The purpose of this research is to find the best combination between substitution cassava flour and glycerol monostearat addition for quality of bread. Experimental design employed in this research is randomized completely design consisting of two factors and three replications, the first factors substitution cassava flour (10%, 20%, and 30%) and the second factor is glycerol monostearat addition (1%,2%,3%,4% and 5%). The best treatment was combination of cassava flour 10% and glycerol monostearat addition 4%. This bread product has taste score 229,5, color score 195 and texture score 236, water content 29,34 %, protein 7,127%, fat 2,793%, starch 47,657%, loaf volume 347%, texture 0,915 mm/gr. det and porous size 1,214 mm2.Keyword : bread, cassava starch flour, glycerol monostearat.